Retrospective analysis of urinary tract infections in long-term care facilities in Japan: Insights from physical examination-based diagnosis - Makoto Hasegawa; Yasuhiro Osugi; Yoshifumi Moriwaki; Yohei Doi (Fujita Medical Journal, 2024)
Objectives: Multidrug-resistant (MDR) bacterial infections are highly prevalent among long-term care facility (LTCF) residents, and are thus important targets for antimicrobial stewardship. Diagnoses of urinary tract infections (UTIs), which are associated with antimicrobial use in these facilities, are not always made by physicians. Past epidemiologic studies have included asymptomatic bacteriuria together with UTIs. The National Healthcare Safety Network has initiated a surveillance program to identify the causative organisms of UTIs in LTCF residents. In Japan, medical care for these residents is provided through in-person physician visits; however, limited related data are available. Therefore, we investigated the organisms causing UTIs and their drug susceptibility among LTCF residents in central Japan, and examined the prevalence of multidrug resistance, its risk factors, and correlations with clinical outcomes.